(untitled) (Research, Society and Development, 2020)
Our objective was to investigate the influence of alternative substrates based on stem decomposed by babassu and humic substances in the production of sunflower seedlings. The experimental design was randomized blocks, in a 3 x 4 factorial scheme (substrate x humic substances). Twelve treatments were studied, T1 (100% babassu stem decomposed (BDS) + 0 ml L-1 HS), T2 (100% BDS + 12.5 ml L-1 HS), T3 (100% BDS + 25 ml L-1 HS), T4 (100% DBS + 50 ml L-1 HS), T5 (50% DBS + 50% LAd + 0 ml L-1 HS), T6 (50% DBS + 50% LAd + 12, 5 ml L-1 HS), T7 (50% DBS + 50% LAd + 25 ml L-1 HS), T8 (50% DBS + 50% LAd + 50 ml L-1 HS), T9 (100% LAd + 0 ml L-1 HS), T10 (100% LAd + 12.5 ml L-1 HS), T11 (100% LAd + 25 ml L-1 HS) and T12 (100% LAd + 50 ml L-1 HS). Each treatment was performed in four replications with one seedling per plot, totaling 48 plots. The DBSxHS interaction provided increases in root length, root volume, basal diameter, number of leaves, plant height and parameters related to inflorescence. The substrate with 100% decomposed babassu stem, together with the dose of 12.5% humic substance, is the best option for producing ’IAC Uruguay’ sunflower seedlings. Further research on the use of DBS and HS is needed to address the use and purpose in producing new crops.